Flexible PVDF/CNTs/Ni@CNTs composite films possessing excellent electromagnetic interference shielding and mechanical properties under heat treatment. (December 2019) - Zeng, Shuiping; Li, Xiping; Li, Mengjia; Zheng, Jiajia; E, Shiju; Yang, Wenjie; Zhao, Biao; Guo, Xiaoqin; Zhang, Rui
Abstract: Lightweight, flexible composite materials with high-efficient electromagnetic interference (EMI) shielding and mechanical performances play a vital role in achieving electromagnetic protection field. In this work, the chain-like Ni@CNTs hybrids are in-situ synthesized by solvothermal method and then the flexible PVDF/CNTs/Ni@CNTs composite films are prepared by solution casting and compression molding. The significant effects of the CNTs or Ni@CNTs on the electrical conductivity and electromagnetic interference (EMI) shielding performance of PVDF/CNT/Ni@CNTs flexible composites were discussed. Thanks to the unique structure of Ni@CNTs, the flexible PVDF/CNTs/Ni@CNTs composite films exhibit ultrahigh efficient EMI shielding properties, with a maximum SE/thickness(d) of 102.8 dB mm −1, which is the highest value reported to date. Furthermore, the heat treatment process on the properties of the flexible composite films was investigated. After heat treatment process, the EMI shielding performance of the composite films is improved by about 10%, which is attributed to the weak movement of the conductive fillers caused by the polymer chains rearrangement. Moreover, the as-prepared composites exhibit excellent mechanical properties, with an average tensile strength of 70 MPa and a mean elongation at break of 16.9%, presenting that the as-prepared composites possess outstanding flexibility and stretching properties. Graphical abstract: Image 1